Role of technology-enhanced learning environment at universities in shaping teachers’ professional identity - Chervova, Albina A.; ZaytsevаSvetlana A.; Kiselev, Gennady M.; Galina E. Muravyova, Aleksey A. Mikhailov; Mikhail V. Sheptukhovsky, Elena I. Rzaeva, Elena V. Sitnova (Opción, 2019)
The research objective is to develop and implement the model of the technology-enhanced learning environment of pedagogical universities, meeting the needs of today’s digital society, complying with the requirements of legislation and facilitating would-be teachers’ training for effective professional activities. The study is based on environment-oriented, competence-oriented, culturological, and informational approaches. The main result is the developed structure of the technology-enhanced learning environment of universities, consisting of four blocks. In conclusion, the use of TELE tools considerably changes the role and essence of interaction between the educational process subjects. Students’ interests, cognitive needs and psychological characteristics become high priority issues.